Assessment of myocardial deformation by CMR tissue tracking reveals left ventricular subclinical myocardial dysfunction in patients with gynecologic cancer undergoing chemotherapy - Tao, Kai; Ye, Lu; Xu, Yan-Jia-Ni; Yang, Meng-Xi; Yin, Ru-Tie; Li, Qing-Li; Lin, Xiao-Juan; Li, Ke-Min; Song, Liang; Ma, Yu; Zhong, Lan; Hu, Ying; et al. (Frontiers in Oncology, 2025)
BackgroundChemotherapy-induced cardiotoxicity is a concern for patients with gynecologic cancer. This study aimed to assess left ventricular (LV) myocardial deformation in patients with gynecologic cancer undergoing chemotherapy and to investigate the association between myocardial deformation and chemotherapy factors.MethodsCardiac magnetic resonance (CMR) was performed to assess LV deformation parameters using CMR tissue tracking based on cine images. Serum myocardial injury biomarker were measured. Deformation parameters were compared between healthy controls and patients. Changes in deformation were assessed as chemotherapy progressed. Correlations between LV deformation parameters, clinical characteristics, and serum myocardial injury biomarkers were also analyzed.ResultsA total of 86 patients with gynecologic cancer and 30 normal controls were included. Among the patients, 41 completed CMR follow-up with a median interval of 6 months. Compared to the controls, patients exhibited lower absolute value of global radial strain (GRS) (37.30 ± 8.94% vs. 44.32 ± 8.44%), global circumferential strain (GCS) (-22.12 ± 3.05% vs. -24.08 ± 2.13%) and global longitudinal strain (GLS) (median -15.72% [IQR-17.13 to -13.58%] vs. -17.51 ± 2.00 %) (all p < 0.05). Patients with preserved LV ejection fraction (LVEF) also showed impaired global strain (all p < 0.05). GRS (39.71 ± 8.09% vs. median 30.56% [IQR 26.52 to 38.15%]; p = 0.001), GCS (-23.45 ± 2.09% vs. median -19.71% [IQR -21.71 to -19.10%]; p < 0.001) and GLS (-16.17 ± 2.42% vs. median -12.12% [IQR -14.10 to -8.53%]; p< 0.001) further decreased as the number of chemotherapy cycles increased during follow-up (all p < 0.05). Multivariate analysis showed that GCS was independently associated with the number of chemotherapy regimens (Standard regression coefficient [β] = 0.397, p < 0.001).ConclusionsMyocardial deformation is more sensitive than LVEF in detecting subclinical left ventricular dysfunction in patients with gynecologic cancer undergoing chemotherapy. GCS was associated with the number of chemotherapy regimens.